Perbandingan Kinerja Antar 3 Perusahaan pada PT Gudang Garam Tbk, PT HM Sampoerna Tbk dan PT Indonesia Tobacco Tbk Periode 2019-2023 - Diah Indri Anggriyanti; Cailah Nasywa Afrila; Dela Wahyu Putri Awanda (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study discusses the comparison of the financial performance of three tobacco companies in Indonesia, namely PT Gudang Garam Tbk, PT HM Sampoerna Tbk, and PT Indonesia Tobacco Tbk in the 2019-2023 period. The analysis was conducted using financial ratios including liquidity, activity, solvency, profitability, and market to evaluate the operational performance and financial structure of each company. The results showed that PT HM Sampoerna Tbk consistently had the best performance in terms of operational efficiency, profitability, and solvency. Meanwhile, PT Gudang Garam Tbk excels in dividend policy, despite facing challenges in asset efficiency and profitability. PT Indonesia Tobacco Tbk, despite showing improvement in some solvency ratios, still faces high financial risk and low operational efficiency. This study provides important insights for investors and stakeholders to understand the competitive position and opportunities for improvement of corporate strategies in the tobacco industry.